Experience of the implementation of active training methods in the teaching methodology of psychological and pedagogical cycle disciplines - Артюхова, В. В.; Щокіна, Н. Б. (Scientific notes of the pedagogical department, 2018)
The article analyzes the possibilities of active teaching methods, particularly the quest method in the professional training of cadets in learning of disciplines of a psychological and pedagogical orientation. The authors analyze the essence of the concept of "quest", its structure, approaches to classification, conditions for implementing quests in the professional training of cadets. The experience of using quests in the teaching of psychological and pedagogical disciplines is presented.